Diversion or Democratization: Do Rural, Hispanic, Community College Students Show Signs of Academic Undermatch?. (January 2017) - Freeman, Eric
This study examines the relationship between academic undermatch theory and the college-going decisions, experiences, and aspirations of first-generation, rural Hispanic community college students in the new destination meatpacking town of Winstead, Kansas. Ethnographic data from rural high school guidance counselors, community college faculty, and students suggest a need to emend the theory to address dynamic contextual factors such as proximity to home, familismo, place attachments, social networks, geographic location, sense of belonging, and academic validation.